PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SD INPRES 17 REMU KOTA SORONG - Darnanengsi Darnanengsi; Darniati Darniati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2020)
This research was conducted to find out how the teacher's role in increasing student motivation in the learning process. The purpose of this study was to find out how the role and efforts of teachers in increasing students' learning motivation. This research is descriptive qualitative research. The results of this study stated that the teacher's role in increasing student motivation at SD Inpres 17 Remu Sorong City was by giving assignments, training to students, then the teacher providing reinforcement, approach, and guidance by conducting meaningful learning as a facilitator and mentor when students have difficulty in the learning process. The teacher's efforts in increasing student learning motivation are by using approach methods, peer tutors, home visits and are given reinforcement by embracing students so that students are active in learning and work together with schools, government, and parents to achieve good learning outcomes.